Kualitas Pelayanan Karyawan Indomaret Ranotana Weru Kecamatan Wanea Kota Manado - Retor, Alexander Christoffel; Porajouw, Oktavianus; Waney, Nordy Fritsgerald Lucky (AGRI-SOSIOEKONOMI, 2023)
This research aims to describe the service quality of Indomaret Ranotana Weru employees, Wanea District, Manado City. This research was conducted for 3 months starting from April to June 2023. The method used in this research was a survey method by taking primary and secondary data. The sampling method in this research was the accidental sampling method. This research was analyzed descriptively and presented in table form. Based on the research results, it shows that the service quality of Indomaret Ranotana Weru employees, Wanea District, Manado City received service quality assessment results in the high category with a percentage of 59.44%. Of the 6 indicators of service quality, 4 indicators were in the high category, namely speed of service, appearance, products and public facilities, and 2 indicators were in the medium category, namely responsiveness and attitude.